Belt-induced abdominal injuries in recent frontal impact CIREN cases. (19th October 2021) - Halloway, Dale; Hauschild, Hans; Pintar, Frank; Yoganandan, Narayan
Abstract: Objective: The objective is to report sex-related variation in 3-point belt–related abdominal injuries in Crash Injury Research Engineering Network (CIREN) cases. Methods: A query of CIREN cases was made for those with the highest ranked Collision Deformation Classification (CDC) to the front plane, a principal direction of force (PDOF) ±20° from 0°, and Abbreviated Injury Scale (AIS) 2+ abdomen injuries attributed to the seat belt. Patterns of injury were categorized as above the crest of the ilium, injuries below the crest of the ilium, and injuries above and below the ilium. This was done in the context of autonomous vehicle occupant kinematics testing results. Twelve 5th and 95th percentile 3-point belt–restrained postmortem human subjects were subjects; test speeds and recline angles varied. Abdomen injuries were anticipated; none were observed. Results: Thirty-five occupants with belt-related abdominal injuries were identified. Seventeen case occupants sustained an injury only within the pelvic contents: 5 women and 12 men. Nine of the 17 were at or above the 81st percentile for height, 13 were between the 62nd and 80th percentile for height, and 4 were less than the 50th percentile for height. Conclusions: The stature component of the body mass index (BMI) appears to be a plausible candidate for an independent variable that is a contributing factor explaining the incidence of pelvic contents injuries when a 3-point belt–restrained occupant is involved in a frontal impact.